Dress like an Egyptian a study of the representation of ancient Egyptian clothing, jewellery, and bodily adornments in music videos of the late-twentieth century and early twenty-first century - Boltman, Aqeelah (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.